Identification of an activated neutrophil phenotype in polymyalgia rheumatica during steroid treatment: a potential involvement of immune cell cross-talk. (4th April 2019) - Nadkarni, Suchita; Lashin, Hazem; Hollywood, Jane; Dasgupta, Bhaskar; Mason, Justin C.; Perretti, Mauro
Abstract : We have reported the existence of a distinct neutrophil phenotype in giant cell arteritis (GCA) patients arising at week 24 of steroid treatment. In the present study, we investigated whether longitudinal analysis of neutrophil phenotype in patients with polymyalgia rheumatica (PMR) could reveal a novel association with disease status and immune cell cross-talk. Thus, we monitored PMR patient neutrophil phenotype and plasma microvesicle (MV) profiles in blood aliquots collected pre-steroid, and then at weeks 1, 4, 12 and 24 post-steroid treatment. Using flow cytometric and flow chamber analyses, we identified 12-week post-steroid as a pivotal time-point for a marked degree of neutrophil activation, correlating with disease activity. Analyses of plasma MVs indicated elevated AnxA1+ neutrophil-derived vesicles which, in vitro, modulated T-cell reactivity, suggesting distinct neutrophil phenotypic and cross-talk changes at 24 weeks, but not at 12-week post-steroid. Together, these data indicate a clear distinction from GCA patient neutrophil and MV signatures, and provide an opportunity for further investigations on how to 'stratify' PMR patients and monitor their clinical responses through novel use of blood biomarkers.